EDUKASI BAHAYA MEROKOK DI DUSUN JARANAN, BANGUNTAPAN, BANTUL - Rissa, Mexsi Mutia; Eko Arianto, Machfudz; Rudi Yulianto; Anisa Putri Wijayanti; Lusiana, Nur Ema Nafa; Nazhifah Nurliyanti Aqilah; Ade Yusfia Wardani; Feti Pusvita Sari (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Smoking behavior is an activity that is often encountered in everyday life. In 2019, the number of global active smokers reached around 940 million men and 193 million women aged 15 years or older. According to the 2013 Riskesdas report, around 66.9% of residents of the Special Region of Yogyakarta (DIY) aged ? 10 years are exposed to cigarette smoke at home. In 2018, this exposure figure increased to 68.6%. The prevalence of smokers in DIY reached 23.9%, and as many as 59.9% of them still smoked at home. The aim of this community service activity is to increase public knowledge about the dangers of smoking. The activity was carried out in Jaranan Banguntapan Hamlet, Bantul. The people targeted in this activity were 31 gentlemen. The method used is lectures and showing audio-visuals. The results of outreach regarding education on the dangers of smoking showed positive results, where there was an increase in public knowledge of the dangers of smoking.